Professors' Foreign Travel Expenses: Deductible or Non-deductible? - Burns, Jane O. (The Accounting Review, 1978)
ABSTRACT: Numerous court cases indicate that individuals traveling abroad are not cognizant of the federal income tax implications. As a result, deductions are lost for trips inadequately planned by uninformed taxpayers. Recent legislation contained in the 1976 Tax Reform Act further complicates this problem. This article examines federal income tax legislation and pertinent court cases relating to foreign travel. The objective is to enable the professor and his family to guard against loss of significant tax deductions when traveling abroad. The knowledgeable professor who carefully plans a trip, with attention to the details, improves his chances of obtaining and defending deductions claimed on the income tax return.